The Impact of the New Normal Era on Investor Trading Behavior: Evidence from the IDX Capital Market School, Central Kalimantan Province, Indonesia - Wardani, Ocmi Nidia; Meina Wulansari Yusniar (HM Publisher, 2024)
The COVID-19 pandemic and the subsequent